Effects of achilline on lipid metabolism gene expression in cell culture - A. V. Ratkin; Iu. A. Pfarger; O. A. Kaidash; V. V. Ivanov; M. M. Tsyganov; V. S. Chuchalin; S. M. Adekenov; V. V. Novitsky (Бюллетень сибирской медицины)
Objective. Evaluation in vitro of the mechanisms of the hypolipidemic effect of sesquiterpene γ-lactone achilline in the hepatoma tissue culture (HTC).Materials and methods.The influence of sesquiterpene γ-lactone achilline and gemfibrozil (comparison drug) on the viability, lipid content and expression of key genes of lipid metabolism in the hepatoma tissue culture. The lipid content was assessed by fluorescent method with the vital dye Nile Red, the cell viability was assessed using MTT assay.Results. Cultivation of of cell cultures of rat’s hepatoma cell line HTC for 48 h with achilline in a concentration of from 0.25 to 1.0 mm and gemfibrozil from 0,25 to 0,5 mm did not change cell viability compared to control. In these same concentrations of the test substance reduced the lipid content in the cells, assessed by fluorescent method with the vital dye Nile Red. To study the mechanism of hypolipidemicaction of achillinedetermined the expression of key genes of lipid metabolism in cell culture lines HTC. The possible mechanism of hypolipidemic action of achilline can be attributed to the increased transport and oxidation of long-chain fatty acids in mitochondria, as evidenced by the increase in the gene expression of carnitine-palmitoyltransferase 2 (Cpt2). The decrease in cholesterol level may be due to increased synthesis of bile acids from cholesterol, due to increased gene expression of 7-alphahydroxylase (Cyp7a1). Conclusion. In cell cultures of rat’s hepatoma cell line HTC sesquiterpene γ-lactone achilline reduces the accumulation of lipids in cells, as evidenced by the decrease in the fluorescence of Nile Red, increased gene expression of the carnitine-palmitoyltransferase 2 (Cpt2) gene and 7-alpha-hydroxylase (Cyp7a1).